Astragalus Polysaccharide Reduces Blood Pressure, Renal Damage, and Dysfunction Through the TGF-β1-ILK Pathway - Zheng, Wei; Huang, Tao; Tang, Qi-Zhen; Li, Shi; Qin, Jie; Chen, Feng (Frontiers in Pharmacology, 2021)
Aim: Astragalus polysaccharides (APS) has anti-oxidant and anti-inflammatory roles in treating several diseases. However, whether APS protects against renal damage in hypertensive mice was still obscure. Methods: By use of hematoxylin-eosin (H&E) staining, immunohistochemistry (IHC), real time PCR and western blotting analysis, the effect and underlying mechanism of APS on renal damage in both DOCA-salt and Angiotensin II induced hypertensive mice was investigated. Results: Our data demonstrated APS significantly reduced the blood pressure in DOCA-salt and Angiotensin II treated mice. Furthermore, APS reduced the inflammation response and renal fibrosis thereby improving the renal function. Furthermore, the level of serum creatinine, urea nitrogen and uric acid enhanced in DOCA-salt treated mice was alleviated by APS administration. In molecular level, DOCA-salt and Angiotensin II increased mRNA level of IL-1β, IL-6, α-SMA, collagen I and collagen III, APS significantly inhibited these effects. Mechanically, APS inhibited TGF-β1/ILK signaling pathway which was activated in hypertensive mice caused by DOCA-salt. Conclusion: Our results suggest that APS played a beneficial role in improving renal dysfunction of hypertensive mice.